ANALISIS YURIDIS TERHADAP PENEGAKAN HUKUM MODIFIKASI KENDARAAN BERMOTOR RODA DUA YANG MENGALAMI PERUBAHAN DIMENSI DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Pius Nifatere Jokhe; Amad Sudiro (Fakultas Hukum Universitas Tarumanagara, 2021)
Motorcycles that were previously only used as a means of transportation, now have another function, namely as an identity function for the owner. Modified motorbikes that have changed dimensions are currently being loved by various groups from young people to the elderly, but the existence of these modified vehicles is still not in accordance with the terms and conditions provided by law to obtain and use modified motorbikes. undergoing a dimensional change. In this study, the author uses a normative research method. Based on the data that has been obtained and analyzed by the author, the lack of firmness by law enforcement officers in taking action against these violations is one of the reasons why many modified motorcycles have changed dimensions and can move freely on the highway. Also, the weak level of socialization provided adds to the lack of public awareness to know the procedures and requirements that must be met in order to be able to modify a motorcycle. The existence of a motorized vehicle that has been modified with a change in type without conducting a type test first will greatly endanger the safety and security of motorists and other road users